Detection of cytokine mRNA production in infiltrating cells in proliferative vitreoretinopathy using reverse transcription polymerase chain reaction. Issue 11 (1st November 1999) - El-Ghrably, I A; Dua, Harminder S; Orr, Gavin M; Fischer, David; Tighe, Patrick J
Abstract : AIMS: To determine whether the infiltrating cells in the vitreous and subretinal fluid of patients with proliferative vitreoretinopathy (PVR) express messenger RNA for various cytokines found in this condition. METHODS: The presence of mRNA coding for HPRT, IL-6, IL-1β, IL-8, and TNFα was investigated in 20 vitreous and subretinal fluid (SRF) samples from patients with PVR by reverse transcriptase polymerase chain reaction (RT-PCR). 16 samples from patients with retinal detachment and macular holes were used as controls. RESULTS: HPRT was detected in all samples of PVR and in 11 (69%) control cases. Patients with PVR demonstrated mRNA for the cytokines tested more often than controls. The difference was statistically significant. CONCLUSION: The presence of mRNA encoding for IL-6, IL-1β, IL-8, and TNFα is significantly detected by RT-PCR in vitreous and SRF samples of patients with PVR, indicating local production of these cytokines by vitreous and SRF cells.